The Effect of Regular Sports Activities on College Students' Concentration Levels and Academic Achievement - Tasya, Amalia (PT. Anagata Sembagi Education, 2025)
Regular sports activities play an important role in maintaining physical health while supporting students' cognitive function, especially concentration and academic achievement. However, the increasing sedentary lifestyle among students poses a risk of a decline in the quality of learning and academic achievement. This study aims to analyze the influence of regular exercise on students' concentration and academic achievement. The method used was a quasi-experiment with a pre-test/post-test control group design involving 80 undergraduate program students who were divided into an experimental group (n=40) and a control group (n=40). The experimental group followed a regular exercise program (jogging, futsal, and aerobic gymnastics) three times per week for eight weeks, while the control group was given no treatment. Concentration is measured using the Stroop Test and the Digit Span Test, while academic achievement is measured through the Cumulative Achievement Index (GPA). Data analysis was performed using t-tests, ANOVA, and regression with SPSS. The results showed that regular exercise had a significant effect on increasing student concentration (p<0.01) and made a positive contribution to increasing GPA, although the effect was small to moderate. Concentration was shown to play a role as a partial mediator of the relationship between sport and academic achievement (R²=0.22). This research confirms that exercise not only maintains physical fitness, but also serves as a strategy to support learning in college. The practical implication is that universities need to integrate sports programs in the curriculum and students are encouraged to make sports a regular part of their academic lifestyle.